Wireless Networks (Attacks ‎‏–‏Security): A Review (Journal of University of Babylon for Engineering Sciences, 2022)
Wireless network security is an important, influential, and effective part of defending wireless networks from intrusions and security holes caused by hackers and attackers. This paper conducted a review of wireless network security requirements, including authentication, confidentiality, availability, and integrity, as well as attacks against wireless networks based on these requirements, most notably Man in the Middle Attack, Eavesdropping, and Denial of Service attack. In addition, some steps were reviewed that would protect and secure wireless networks from hacker attacks.